Primary interhemispheric subdural empyemas: A report of three cases and review of literature - Ravindranath Kapu; Anil Pande; M.C. Vasudevan; Ravi Ramamurthi (Indian Journal of Neurosurgery)
Background Interhemispheric subdural empyema is an uncommon condition and is considered neurosurgical emergency. These are generally seen following neglected otorhinological infection, but may be posttraumatic or iatrogenic in origin. The source of infection can be frequently found, but in few cases no source of infection can be identified, called idiopathic empyemas. These idiopathic interhemispheric subdural empyemas are even rare. They can present with a rapid progression of symptoms and can carry poor prognosis. Early intervention with craniotomy and appropriate antibiotics can improve the condition of these patients.